Sex differences in body composition, metabolism‐related hormones, and energy homeostasis during aging in Wistar rats - Quirós Cognuck, Susana (Physiol Rep, 2020)
Aging affects the body composition and balance of energy metabolism. Here, we collected in a single work several physiological parameters to show how aging and sex differences can influence energy homeostasis. Body mass index (BMI), Lee index, glucose tolerance, glycemia, and lipidogram in fasting were measured in male and female Wistar rats at the ages of 2, 6, 9, 12, and 18 months. We also measured the lipid profile, free fatty acids, glycerol, glycemia, leptin, adiponectin, insulin, corticosterone (CORT), prolactin (PRL), thyroid stimulated hormone, and triiodothyronine (T3) in 3‐ and 18‐month‐old rats of both sexes, fed ad libitum. Animals were classified as obese beginning at 2 months in males and 6 months in females. Aged male rats showed hyperglycemia and glucose intolerance compared to young males and old females. In the ad libitum condition, the 18‐month males presented higher serum levels of triglycerides, total cholesterol, and free fatty acids than females. The 18‐month‐old females had higher PRL and CORT concentration than males, but insulin and T3 were higher in 18‐month‐old males than females. Our work demonstrated that aging processes on energy metabolism in rats is sex specific, with a better lipid profile and glucose tolerance in aged females.